Novel Biocomposite Films Based on High Methoxyl Pectin Reinforced with Zeolite Y for Food Packaging Applications - Aleksandra Nesic; Sladjana Meseldzija; Gustavo Cabrera-Barjas; Antonije Onjia (Foods, 2022)
Pectin is a natural biopolymer with broad applications in the food industry and it is suitable to prepare edible films to prolong food shelf-life. However, the main limitation of pectin-based films is their poor mechanical and barrier properties. Zeolite Y is a hydrophobic clay that can be used as film reinforcement material to improve its physicochemical and mechanical properties. In this work, the influence of high methoxyl citrus and apple pectin on physicochemical properties of biopolymer films modified with zeolite Y (0.05–0.2 wt%) was investigated. The films were characterized by FTIR, TGA, WAXD, mechanical analysis, and water vapor permeability analysis, and a potential film application is presented. The WAXD and FTIR analysis demonstrated that the strongest interaction between pectin chains and zeolite Y occurred when citrus high methylated pectin was used. Adding 0.2 wt% of zeolite Y into citrus high methylated pectin matrix enhanced the tensile strength by 66%, thermal stability by 13%, and water vapor barrier by 54%. In addition, fruit shelf-life test was performed, where strawberries were sealed in film. It was shown that sealed strawberries maintained a better color and healthy appearance than the control treatment after 7 days at 10 °C. This study enabled the development of biocomposite films with improved properties for potential application in food packaging.